Fast Holographic Deconvolution: A New Technique for Precision Radio Interferometry - Sullivan, I.; Morales, M.; Hazelton, B.; Arcus, Wayne; Barnes, D.; Bernardi, G.; Briggs, F.; Bowman, J.; Bunton, J.; Cappallo, R.; Corey, B.; Deshpande, A.; et al. (Institute of Physics Publishing, Inc., 2012)
We introduce the Fast Holographic Deconvolution method for analyzing interferometric radio data. Our new method is an extension of A-projection/software-holography/forward modeling analysis techniques and shares their precision deconvolution and wide-field polarimetry, while being significantly faster than current implementations that use full direction-dependent antenna gains. Using data from the MWA 32 antenna prototype, we demonstrate the effectiveness and precision of our new algorithm. Fast Holographic Deconvolution may be particularly important for upcoming 21 cm cosmology observations of the Epoch of Reionization and Dark Energy where foreground subtraction is intimately related to the precision of the data reduction.